2006
DOI: 10.1080/09540120500521053
|View full text |Cite
|
Sign up to set email alerts
|

Immunisation coverage among children born to HIV-infected women in Rakai district, Uganda: effect of voluntary testing and counselling (VCT)

Abstract: To evaluate the impact of maternal HIV-infection on routine childhood Immunisation coverage, we compared the Immunisation status of children born to HIV-infected and HIV-uninfected women in rural Uganda. The study population was 214 HIV(+) and 578 HIV(-) women with children aged 6 to 35 months previously enrolled in a community study to evaluate maternal and child health in Rakai District, Uganda. Sampling of subjects for interview was stratified by the use of voluntary counselling and testing (VCT) service so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 34 publications
1
19
0
1
Order By: Relevance
“…Mothers who perceived that irrespective of the absolute values, distance to the immunisation centre can be overcome are more than four times more likely to get their children immunised (OR 4.52, CI 2.14–9.55). This is consistent with Mast et al ‘s conclusion in Uganda 24 that immunisation coverage in venues difficult to reach had odds of immunisation more than four times those venues easy to reach. Jamil et al cited in Chowdhury 25 maintained that children living far from immunisation venues were 30% less likely to be fully immunized compared with children living nearby.…”
Section: Discussionsupporting
confidence: 91%
“…Mothers who perceived that irrespective of the absolute values, distance to the immunisation centre can be overcome are more than four times more likely to get their children immunised (OR 4.52, CI 2.14–9.55). This is consistent with Mast et al ‘s conclusion in Uganda 24 that immunisation coverage in venues difficult to reach had odds of immunisation more than four times those venues easy to reach. Jamil et al cited in Chowdhury 25 maintained that children living far from immunisation venues were 30% less likely to be fully immunized compared with children living nearby.…”
Section: Discussionsupporting
confidence: 91%
“…One reason for this increased mortality may be that children born to HIV-positive mothers are less likely to receive routine childhood vaccinations. HIV-positive mothers may be too weak or too poor to bring their children to vaccination clinics (Mast et al 2006; Eley 2008) or they may be reluctant to access primary health care clinics for fear of stigma (Aggleton & Parker 2002). HIV infection may also be an indicator of relatively high tolerance of health risks in general, and mothers who are more tolerant of risks to their own health may be less motivated to ensure that their children receive risk-reducing interventions, such as vaccinations (Mast et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, health care staff responsible for immunization delivery may miss opportunities for immunizing HIV-infected children because they are unaware of those recommendations, they are concerned about greater risk with use of vaccines in this population, or other reasons. African [4, 5] and European studies [6,7, 8] found lower immunization coverage of HIV-infected children compared to uninfected peers, while a North American study found equally low vaccine coverage, for both HIV-infected and the HIV-exposed uninfected populations for some vaccines [9]. In a rural South African population, maternal HIV-positive status was independently associated with lower vaccination rates for four vaccines in children 12–23 month of age (BCG, DTP3, poliomyelitis, and hepatitis B) [10].…”
mentioning
confidence: 99%